2011
DOI: 10.1530/rep-10-0299
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of bone morphogenetic protein 4 in reproductive organs of female mice

Abstract: Various members of the bone morphogenetic protein (BMP) family have been shown to regulate mammalian follicular development by affecting granulosa cell proliferation and steroidogenesis. In situ hybridization studies have shown expression of BMPR1A, BMPR1B, and BMPR2 in the granulosa cells and oocyte of most of the follicles in the ovary, suggesting that these cells have the capacity to respond to BMP signaling. Although much is known about BMP4 signaling, its expression pattern in the female reproductive trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
4
21
1
Order By: Relevance
“…In support of this, we have found that while the expression of BMPRIB was detectable in follicular cells of mouse primordial follicles, FSHR was absent but later appeared in primary follicles. These data together with a previous report in rat (Moore & Shimasaki 2005) contradict previous reports (Meredith et al 1992, Flaws et al 1997 and therefore suggest the presence of a complex interplay between gonadotrophins and other growth factors such as BMPs where direct and indirect cross-signalling regulates ovarian function (Tanwar & McFarlane 2011). The reported decrease in primordial follicles after eCG treatment (Tanwar et al 2008) conflicts with the present result probably due to the manual counting method used in the previous study instead of the automated stereology used in this work.…”
Section: The Role Of Bmps In Ovarian Functioncontrasting
confidence: 97%
See 3 more Smart Citations
“…In support of this, we have found that while the expression of BMPRIB was detectable in follicular cells of mouse primordial follicles, FSHR was absent but later appeared in primary follicles. These data together with a previous report in rat (Moore & Shimasaki 2005) contradict previous reports (Meredith et al 1992, Flaws et al 1997 and therefore suggest the presence of a complex interplay between gonadotrophins and other growth factors such as BMPs where direct and indirect cross-signalling regulates ovarian function (Tanwar & McFarlane 2011). The reported decrease in primordial follicles after eCG treatment (Tanwar et al 2008) conflicts with the present result probably due to the manual counting method used in the previous study instead of the automated stereology used in this work.…”
Section: The Role Of Bmps In Ovarian Functioncontrasting
confidence: 97%
“…The antibodies were raised and characterised in our laboratory as described previously (Tanwar & McFarlane 2011). In brief, the synthetic peptides were conjugated to diphtheria toxoid (CSL) and emulsified in Freunds complete adjuvant (Sigma-Aldrich Pty Ltd) for the primary vaccination and in Freunds incomplete adjuvant for booster injections.…”
Section: Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…BMPR1B is expressed from secondary to atretic follicles and is the receptor for BMP2, -4, -6, and -7. BMPR1B gene KO and mutations have an adverse effect on fertility (compromised cumulus expansion) in mice and in humans (Tanwar & McFarlane 2011). This gene, which responds to BMP15, is also a good candidate for a granulosa signaling back to the oocyte.…”
Section: Gene Analysismentioning
confidence: 99%